Hybrid inorganic-organic capsules for efficient intracellular delivery of novel siRNAs against influenza A (H1N1) virus infection - Timin A. S. Aleksandr Sergeevich; Muslimov A. R.; Petrova A. V.; Lepik K. V.; Okilova M. V.; Vasin A. V.; Afanasyev B. V.; Sukhorukov G. B. (2017, 2017)
Title screen